(untitled) (Revista Contexto & Educação, 2024)
Claiming Physical Education as a curricular component of the area of codes and languages it’s not something new. However, we realize that the traditional and non-critical theory in the curriculum, which historically influenced the curriculum of Physical Education, not only disregard its character of production and sharing of meanings, but also see in Physical Education a possibility of correction of the body understood as "abnormal". Thus, in this essay, we aim to reflect on how difference is addressed in different curricular theories of Physical Education. The information analysis was conducted based on post-structuralist theory. Finally, we consider that the cultural curriculum, by placing culture at the center of pedagogical practices, dialogues and seeks to contribute to the construction of a Physical Education and a world less and less unequal, seeking no more to hide and correct the difference, but rather to maximize it.